PERBEDAAN KUALITAS KERJA SISWA PROGRAM KEAHLIAN TATA BUSANA DI BISNIS CENTER DAN UNIT PRODUKSI - Wijayaningsih, Ratih (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2013)
AbstractThis purposes of the research are to knowing the quality of Students of Fashion Education Program’s works in Fashion Business Center and Production Unit of Pekalongan 1 Vocational School and to knowing the quality differences of Fashion Education Program’s Students’ works in Fashion Business Center and Production Unit of Pekalongan 1 Vocational School. The population in this study were all Students of Fashion Education Program’s works in Fashion Business Center and Production Unit ofPekalongan 1 Vocational School, which were 81 in Business Center and 6 in fashion Production Unit students. Sampling technique used in this research was total sampling. Data Collection were established by using questionnaires, interviews, observation and documentation. Data were analyzed using descriptive analysis and the percentage of chi square to determine whether there was anydifference in the students' works quality in Business Center and Production Unit. The results showed that there were works quality of students worked in the Business Center which was 79%,was classified intogood category; On the other hand, the quality of students works in the Production Unit which was 91%, was classified into excellent category. significant differences (α = 5%) in works quality of students worked in the Business Center and Production Unit with p value of 0.002. The conclusions of this study were works quality of Fashion Education Program Students worked in the Business Centerwasgood, while the quality in the Production Unit counterpart was excellent, and there were differences in the quality among Fashion Education Program Students’ works in Fashion Business Center and Production Unit of Pekalongan 1 Vocational Schooling practical works.